Quantification of the severity of acute cholangitis - Torterolo, Edgardo; Olazábal, Mario; Beltrán, Ricardo; Czarnevicz, Daniel; Ferreira, Ciro; Silva, Celso (Cirugía del Uruguay, 1993)
In spite of advances in the treatment of accute bacterial cholangitis, these still have high morbility and mortality (20%) and frequently represent a therapeutical problem.